Disaster Preparation Knowledge Of Urban And Rural Students At Solo Region - Sunarhadi, R. Muh. Amin; Khoirunisa, Nanda (Fakultas Teknik, Universitas Brawijaya, 2015)
Solo region covers Sukoharjo, Surakarta and Klaten that have been recognized as vulnerable areas for flood and earthquake. This study wants to determine the level of students’ preparedness who attends school in urban and rural areas against floods and earthquakes. The data come from secondary data obtained through research in 2013-2014. 1.150 respondents came from 15 junior high schools. The results show that: 1) the average level of student preparedness against floods is 52.22% and included in the category of less prepared; 2) the average level of preparedness of students to the earthquake is 67.52% and included in the category of prepared; 3) the average level of preparedness of students who attend school in urban areas is 67.72% included in the category of prepared; 4) the average level of preparedness of students who attend school in rural areas is 52.02% and included in the category of less prepared. The study conclude that students who attend school in an urban preparedness higher than students who attend school in rural areas.Keywords: Disaster preparedness, urban and rural, school